Kajian Minimnya Penerapan Keselamatan Dan Kesehatan Kerja (K3) Pada Proyek Gedung Di Bojonegoro - Sujiat, Sujiat (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Occupational Health and Safety is one or an important factor in a job, for example. The purpose of this research is to identify the factors that influence the lack of OSH applications in construction projects in Bojonegoro and analyze the factors that most influence the lack of OSH applications in construction projects in Bojonegoro which will be analyzed with the Regression method. This study used the observation method with a quantitative approach with regression analysis. The results of this study Occupational Safety (K3) in the building project in Bojonegoro have a significant influence. Based on the results of the simultaneous F test, it can be concluded that there is a significant result